Caring for people in pain - Davis, Bryn D. (Routledge essentials for nurses., 2000)
An excellent introduction for nurses to all aspects of pain and its management. Topics examined are relevant to all areas of health care practice and include:*types of pain*the experience of pain, including psycho-social factors*interventions (pharmocological, physical and psychological)*alternative and complementary therapies. Caring for People in Pain clearly sets out the research base for practice and provides a thorough and accessible text for students of this core topic on all entry level and many post-registration nursing courses.